Heterogeneity of the masks: between Bakhtin’s carnival and Discépolo’s grotesco criollo (ALPHA. Journal of Arts, Literature and Philosophy, 2016)
This article attempts to establish a parallel between Mikhail Bakhtin’s concept of carnival’s mask in Rabelais and His World and other writings, and the mask in Grotesco Criollo Theater in Buenos Aires, during the first decades of the twentieth century. The article begins by defining similarities and differences in the use of these two masks. In the medieval case, the mask is used as a tool of equalization and social catharsis, and in the Grotesco Criollo, the mask is articulated as a shaping tool for conformity and social adaptation. Thus, the practical and aesthetic functions of both masks, though complementary in terms of their ingredients (mask/ social function/social order), are opposites in their implementation and community values. The carnival mask is a mask trying to break the established order momentarily, simply to keep it in the end. Instead, the grotesque mask is a mask that operates from within the individual and the family forcing him/ her to stabilize national customs, values, expectations for the suburban immigrant community (foreign and peasant) displaced to Buenos Aires’ periphery to self-ensure their physical survival. However, such insurance often comes at the cost of emotional and social wellbeing of these displaced marginal subjects.
Keywords: Immigration; Argentinian Immigration Theater; Carnavalesque